2021
DOI: 10.3390/app11041658
|View full text |Cite
|
Sign up to set email alerts
|

Smart Coordinate Measuring Machine (CMM) Inspection for Turbine Guide Vanes with Trend Line and Geometric Profile Tolerance

Abstract: Turbine guide vanes are among the most critical and complex turbine parts. As an entire engine comprises a significant number of vanes, simplification of the measurement process translates into overall time and money savings. The key to simplification is to define critical areas for inspection, which enables relaxation of strict inspection standards in all areas of stable process manufacturing. The method described herein can help engineers to achieve savings in inspection time and cost, at the same time ensur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The article [ 27 ] takes into account other elements of a measurement strategy, such as the scanning speed. The influence of the number of measurement points on coordinate measurement results for free-form surfaces was also analysed in [ 28 ]. The authors of [ 28 ] found that the use of 25 points located along cross-sections of a blade is sufficient, and significantly reduces measurement time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The article [ 27 ] takes into account other elements of a measurement strategy, such as the scanning speed. The influence of the number of measurement points on coordinate measurement results for free-form surfaces was also analysed in [ 28 ]. The authors of [ 28 ] found that the use of 25 points located along cross-sections of a blade is sufficient, and significantly reduces measurement time.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of the number of measurement points on coordinate measurement results for free-form surfaces was also analysed in [ 28 ]. The authors of [ 28 ] found that the use of 25 points located along cross-sections of a blade is sufficient, and significantly reduces measurement time. On the other hand, the authors of [ 29 ] proposed a two-stage algorithm for generating a movement path for a measuring probe in the case of five-axis scanning of a product’s surface, which ensures a collision-free measurement.…”
Section: Introductionmentioning
confidence: 99%